Who is Living at the Vicarage? an Analysis of the 1881 Census Returns for Clerical Households in Lincolnshire - Tomlinson, John W. B. (Studies in church history, 2014)
The 1881 census took place on the evening of Sunday 3 April and provides a snapshot of the composition of virtually every household in the UK, including details of age, occupation and birthplace. In Lincolnshire the census returns for 647 ecclesiastical parishes and districts provide a valuable source of information about the households of the clergy. The range of this record, from remote rural villages to urban communities, although limited to one region of the country, can be considered as largely representative of typical clerical households in England in the late nineteenth century.